Bimbingan Teknis Pengelolaan Pembelajaran secara Video Conference dengan aplikasi Zoom dan Youtube di Era Pandemi Covid-19 - Agusriandi Agusriandi; Mutmainnah Mutmainnah; Elihami Elihami; Yunus Busa (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The aims to provide teachers and lecturers with understanding and skills on how to manage learning online or online. This stage of community service includes analyzing the need for an online learning management platform, conducting technical guidance, and conducting evaluations. After the technical guidance activity, the participants liked the material and speakers in the technical guidance which indicated that the participants understood the material presented by the resource persons. Based on the evaluation results it was found that the implementation of this activity was successful with a high level of attendance of the participants, a level of likeness that was evenly distributed in all material presented by the resource persons, and a very high level of satisfaction with the guidance committee services.